Development of e-transport system for UiTM transportation unit / Maimun Ramli - Ramli, Maimun (2006)
E-Transport is the proposed system that builds in order to overcome the problem that facing by the UiTM student, staff and Transportation Unit staff during transport booking process. Before this, the booking process is done manually. Student and staff make a booking by filling the booking form and after that the booking form will be checking by the Transportation Unit's staff. The transport that available to book at Transportation Unit is such as car, lorry, van and bus. Student and staff need to come to Transportation Unit to deal with the responsible staff to make a booking process. This process is not effective because it waste their time and energy. There are many researches done in order to collect data about the transport booking process and how to cater the problem. As a result, E-transport will be build as a web base application that uses PHP, Apache and MySQL as a proposed method. Hopefully, this proposed system will help the UiTM student, staff and Transportation Unit staff during transport booking process